Pengaruh Hafalan Ayat AL-Qur’an terhadap Prestasi Belajar Siswa Mata PelajaranAl-Qur’an Hadits Di Madrasah Ibtidaiyah Al-Azhar Serabi Barat Bangkalan - Subhan Adi Santoso (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract education is a basic necessity for every human being, because with the education that human beings can determine the next steps. In this study the authors use a method of survey with a correlation approach conducted in Madrasah Ibtidaiyah Al-Azhar Serabi Barat Bangkalan by involving class III, IV, V and VI students who participated in the memorization activities of the Qur'an. Data collection is done with observations, polls, and documentaries. Data analysis using correlation analysis with product moment formula correlation technique.The results of the research obtained to answer the formulation of problems are: 1) the application of memorization of the Qur'an in Madrasah Ibtidaiyah Al-Azhar Serabi Barat Bangkalan applied according to the results of observation and based on the results of the poll, hence the result obtained is 55.5. Thus, the average score number of the memorization rate of Al-Quran Madrasah Ibtidaiyah Al-Azhar Serabi Barat Bangkalan is good enough, 2) Student learning achievement on the subjects of the Qur'an hadith in Madrasah Ibtidaiyah Al-Azhar Serabi Barat Bangkalan after the memorization activities of the Qur'an is in good category with an average of 81.92 of the entire respondent, and 3) the influence between memorization of Al-Qur'an with students ' learning achievement in the field of Quranic study in Madrasah Ibtidaiyah Al-Azhar Serabi Barat Bangkalan with medium interpretation. With the correlation number between variable X and variable Y of 0511. Its significance by 5% seen from table Correlation Product Moment.